Hubungan Efikasi Diri dengan Kualitas Hidup Pasien yang Menjalani Hemodialisa di RSUD Embung Fatimah Batam - Sari Utami Muchtar, Rizki; Ennimay; Rudmana, Andryanti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Chronic kidney disease is a progressive disturbance of kidney function that can’t recovered so that need a replacement therapy like hemodialysis. Hemodialysis process can cause physical, psychological and social as well as environmental changes that influence the quality of life. One of the support system that could maximize the quality of life is self efficacy. The quality of life will increase when respondent begin to accept the disease condition and obedient toward treatment process. This research aims to analyse relationship between self-efficacy and quality of life of chronic kidney disease patient that undergo hemodialysis in hemodialysis department of RSUD Embung Fatimah Batam. This study ia a quantitative research that utilized cross-sectional design 48 samples were chosen using total sampling technique. Data was gathered using Chronic Kidney Disease Self Efficacy questionnaire (CKD-SE) and KDQOL SF-36. Data was analyse using chi-square. The result of the study was found that 26 respondents (54,2%) shows high self-efficacy with good quality of life while 22 respondents (45,8%) shows low self-efficacy with poor quality of life (p-value 0,000 < 0,001). As conclusions is there is a relationship between self efficacy and quality of life of chronic kidney disease patient who undergo hemodialysis. Researchers hoping that nurse can develop nursing intervention to build sel efficacy as well as good quality of life chronic kidney disease patient